Сезонные миграции пашенной полевки (Microtus agrestis L.) на субальпийских лугах Черногоры Украинских Карпат. Сообщение II - Пилявсиий, Б.Р. (Вестник зоологии, 1970)
As a result of investigations, carried out in the Ukrainian Carpathians the seasonal migrations are studied of Microtus agrestis under the conditions of high mountains. It was established that the animals, labelled on subalpine meadows in autumn (August — September) in associations of Myrtilletum and Deschampsieturn, migrate to the fir-tree forest of the Carpathian taiga. This phenomenon is conditioned by the worsening of fodder conditions (drying of the plants) on polonines and coincides with the tall of temperature there. In spring (May) of the next year M. agrestis comes back to the polonines. That time they were found in Nardetum, Myrtilletum, Deschampsietum and other places.
In summer and spring the populations of M. agrestis are more settled, in spring and autumn — more movable. The cause lies in the change of plant aspects and decrease oi fodders in the colony.